1996
DOI: 10.1183/09031936.96.09091907
|View full text |Cite
|
Sign up to set email alerts
|

Cysteinyl leukotriene involvement in chronic lung disease in premature infants

Abstract: C Cy ys st te ei in ny yl l l le eu uk ko ot tr ri ie en ne e i in nv vo ol lv ve em me en nt t i in n c ch hr ro on ni ic c l lu un ng g d di is se ea as se e i in n p pr re em ma at tu ur re e i in nf fa an nt ts s A.J. Cook*, B. Yuksel*, A.P. Sampson**, A. Greenough*, J.F. Price* Cysteinyl leukotriene involvement in chronic lung disease in premature infants. A.J. Cook, B. Yuksel, A.P. Sampson, A. Greenough, J.F. Price. ERS Journals Ltd 1996. ABSTRACT: The pathophysiology of chronic lung disease (CLD) in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
(38 reference statements)
0
5
0
2
Order By: Relevance
“…A single study has shown increased urinary leukotriene (LT) E4 in babies with chronic lung disease, compared with controls [15]. There was no correlation with indices of airflow obstruction.…”
Section: Chronic Lung Disease (Cld) Of Prematuritymentioning
confidence: 99%
“…A single study has shown increased urinary leukotriene (LT) E4 in babies with chronic lung disease, compared with controls [15]. There was no correlation with indices of airflow obstruction.…”
Section: Chronic Lung Disease (Cld) Of Prematuritymentioning
confidence: 99%
“…El factor de necrosis tumoral y la IL-6 inducen la producción de fibroblastos y colágeno que están presentes en los niños con DBP 26,30 . También se han encontrado niveles elevados de leucotrienos en pulmón de niños que desarrollan esta patología y que permanecen elevados hasta los 6 meses de edad 31 . Los leucotrienos causan una serie de alteraciones pulmonares como edema intersticial, producción de mucus y especialmente broncoconstricción y vasoconstricción 31 .…”
Section: Infección E Inflamaciónunclassified
“…También se han encontrado niveles elevados de leucotrienos en pulmón de niños que desarrollan esta patología y que permanecen elevados hasta los 6 meses de edad 31 . Los leucotrienos causan una serie de alteraciones pulmonares como edema intersticial, producción de mucus y especialmente broncoconstricción y vasoconstricción 31 . Sin embargo, aún se desconoce cual es el factor que inicia y mantiene la respuesta inflamatoria que termina dañando el pulmón.…”
Section: Infección E Inflamaciónunclassified
“…In vivo, LTE 4 production is often used as an indication of peptide LT turnover [ 28,29] . We have used the production of LTE 4 and LTB 4 by the vessels to assess 5-lipoxygenase activity in these vessels.…”
Section: Figurementioning
confidence: 99%